Cholesterol Accumulation Enhances Cigarette Smoke-Induced Airway Epithelial Inflammation - Jing D; Yu JK; Chen HP; Dong LL; Li W; Li ZY; Zhou JS (International Journal of COPD)
Du Jing,1,2 Jin-Kang Yu,1 Hai-Pin Chen,1 Ling-Ling Dong,1 Wen Li,1 Zhou-Yang Li,1 Jie-Sen Zhou1 1Department of Respiratory and Critical Care Medicine, Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Yuyao People’s Hospital of Zhejiang Province, Ningbo, People’s Republic of ChinaCorrespondence: Jie-Sen Zhou; Zhou-Yang Li, Department of Respiratory and Critical Care Medicine, Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, 310009, People’s Republic of China, Email jason.627@zju.edu.cn; lizhouyang@zju.edu.cnBackground: Statins, commonly used to lower cholesterol, have been shown to have anti-inflammatory effects in respiratory disease models. Disorders of cholesterol metabolism can cause damage to cells and tissues, and further lead to the development of a variety of diseases. However, the role of cholesterol metabolism in cigarette smoke-induced airway epithelial inflammation is unclear. The present study aims to explore this question.Methods: Human bronchial epithelial cells (HBEs) were stimulated with cigarette smoke extract (CSE) and mice were exposed to CS as models. The expression of cholesterol content and cholesterol metabolism-related molecules such as Sterol Regulatory Element-Binding Protein 2 (SREBP2), 3-Hydroxy-3-Methylglutaryl-CoA Reductase (HMGCR), ATP Binding Cassette Transporter A1 (ABCA1), and ATP Binding Cassette Transporter G1 (ABCG1) were detected by cholesterol assay kits and immunohistochemistry (IHC) in vivo, and were detected by cholesterol assay kits, Western blot (WB), and quantitative real-time polymerase chain reaction (Q-PCR) in vitro. Cholesterol metabolism molecules related siRNAs, inhibitors or agonists were used to intervene the Cholesterol levels in HBE. The mRNA level and protein level of interleukin IL-6 and IL-8 were detected by RT-qPCR and enzyme-linked immunosorbent assay (ELISA). Cellular reactive oxygen species (ROS) levels were detected by reactive oxygen species assay kits.Results: We found that cigarette smoke exposure inhibited cholesterol efflux by decreasing the expression of ABCA1, thereby increasing cholesterol accumulation in airway epithelial cells, which promotes the production of reactive oxygen species and promotes the secretion of inflammatory cytokines, ultimately aggravating cigarette smoke-induced airway inflammation. Reducing intracellular cholesterol content by inhibiting intracellular synthesis and promoting increased efflux can reduce the cigarette smoke-induced airway epithelial inflammatory factors secretion.Conclusion: In conclusion, cholesterol accumulation plays an important role in cigarette smoke-induced airway inflammation and may provide new targets in the treatment of this disease in the future.Keywords: airway epithelial cell, cholesterol metabolism, cigarette smoke, inflammation